Sub-100 nm TiO2 tubular architectures for efficient solar energy conversion. Issue 24 (1st June 2016) - Samir, Menna; Salama, Mohamed; Allam, Nageh K.
Abstract : The smaller, the better: sub-100 nm tubes showed enhancement in the performance of solar energy conversion devices. Abstract : Significant enhancement in the performance of solar energy conversion devices has historically been achieved through optimized device scaling. Scaling trends will be extremely difficult to maintain unless new materials and device structures are discovered. Herein, sub-100 nm TiO2 tubular architectures were synthesized, for the first time, via galvanostatic anodization. The fabricated nanotubes are partially crystalline with high photoactivity towards water splitting and solar-to-electric conversion. Mott–Schottky, transient photocurrent and incident photon-to-current efficiency (IPCE) analyses indicate a faster electron transfer at the nanotube/electrolyte interface. The sub-100 nm tubes showed a maximum conversion efficiency of 9.3% upon their use in dye-sensitized solar cell devices. The concept of short nanotubes should be useful for the future use of the material in various applications.